2009
DOI: 10.2166/wst.2009.744
|View full text |Cite
|
Sign up to set email alerts
|

Non-government organisation engagement in the sanitation sector: opportunities to maximise benefits

Abstract: Non-government organisations (NGOs) have long played a role in delivering sanitation services to communities in Southeast Asia and Pacific countries, particularly in rural areas. In contrast with large scale infrastructure focused initiatives, NGO programs commonly focus on building linkages between technical and social realms. Drawing on the breadth and depth of NGO experiences, there are opportunities for NGOs to play a greater role in the sanitation sector and to work in partnership with other actors includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…However, Faniran (2016) also reported that the approach did not yield the desired results in Nigeria. The CLTS, on the contrary, involves facilitating processes to inspire and empower communities to stop open defecation by building and using latrines, without offering external subsidies for the purchase of hardware infrastructure (Carrard et al, 2009;Lüthi et al, 2010: Kar, 2005Woode et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Faniran (2016) also reported that the approach did not yield the desired results in Nigeria. The CLTS, on the contrary, involves facilitating processes to inspire and empower communities to stop open defecation by building and using latrines, without offering external subsidies for the purchase of hardware infrastructure (Carrard et al, 2009;Lüthi et al, 2010: Kar, 2005Woode et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With ‘the availability and sustainable management of water and sanitation for all’ as Goal 6 of the new SDGs (United Nations General Assembly, 2015: 14), NGOs in the WaSH sector have the potential to make lasting change. For example, in a study that consulted over 100 NGOs, strengths such as community partnerships for delivering sanitation services in remote areas and adaptability to local policy contexts allowed NGOs to engage communities in designing locally-appropriate solutions to sanitation (Carrard et al, 2009). Furthermore, as intermediate level actors that sit between national government institutions and service providers, NGOs play an important role in advocating for sustainable and cost-effective development through mediation and collaboration with other actors in the WaSH sector (Carrard et al, 2009; Visscher et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Enabling strengths included their ability to deliver sanitation services to remote places within a short time frame because of community partnerships, as well as their adaptability to meet identified needs in view of different local community and policy contexts (Carrard et al, 2009). Additionally, as intermediate level actors that sit between national government institutions and service providers, NGOs can advocate for sustainable and cost-effective development through mediation and collaboration with other actors in the water, sanitation and hygiene (WaSH) sector (Visscher et al, 2006;Carrard et al, 2009). In a case study on sanitation in Uganda, NGOs were involved in a variety of activities; they took part in a working group with government ministries, helped a district develop their own strategic framework and partnered with the private sector and local NGOs to support latrine construction (Visscher et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Development evaluation can be used to test assumptions behind development interventions and even bring NGOs' strengths to the forefront, particularly small or ‘grassroots‐level’ NGOs that are common in water‐based development. For example, in a study that consulted over a hundred NGOs to understand their role in the sanitation sector, NGOs were found to successfully engage communities in designing locally appropriate solutions to sanitation (Carrard, Ped, Willetts, & Powell, ). Enabling strengths included their ability to deliver sanitation services to remote places within a short time frame because of community partnerships, as well as their adaptability to meet identified needs in view of different local community and policy contexts (Carrard et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation